Carta da Vegetação Natural Potencial de Caldas da Rainha - Carlos Neto (Finisterra - Revista Portuguesa de Geografia, 2008)
This article presents and discusses a Potential Natural Vegetation (PNV) Map of the Caldas da Rainha Municipality. After outlining the concept, an assessment is made of the conditioning factors that affect the PNV (soil, geology, lithology, bioclimate). A model allowing for the estimation of the PNV is then put forward based on a correspondence drawn between the PNV and the relevant biotopic variables. The resulting PNV map was validated through comparison with the vegetal communities effectively present in the field. The PNV Map of Caldas da Rainha shows that almost the entire area of this Municipality corresponds to potential cork-oak, Portuguese-oak, elm and willow forests. Cork-oak forests are associated with podzolic soils, made up of sand and sandstone; Portuguese-oak forests (Quercus faginea subsp. broteroi) occur in the presence of limestones, clays, and dolomites; whereas willow and elm forests are associated with the floodplains of the hydrographical unit called the Ribeiras do Oeste. Finally, it is worth noting that the most relevant features in terms of protection and conservation (due both to their rarity and to the presence of endemic species) are to be found in complex communities: halophytic (Óbidos lagoon), psammophilous, rupicolous and peat bogs.